3PC-032 Low-dose morphine solution for spinal anaesthesia – ready to use to improve patient safety in drug therapy. (March 2019) - Lämmle, K; Kirchhoff, A; Hoffmann, P; Amann, S
Abstract : Background: Combination with a local anaesthetic agent, such as bupivacaine and a lipophilic opioid such as sufentanil, is frequently used in intrathecal anaesthesia for caesarean section. The combination with low-dose morphine solution 100 to 200 µg reduces wound pain after surgery. No drug with low-dose morphine solution is licensed in Germany. Available products need dilution by factor 100. This two-step diluting procedure involves high risks of contamination and overdosing, the latter resulting in respiratory depression with delayed onset. Purpose: Therefore, anaesthesiologists requested the hospital pharmacy to supply a 100 µg/ml morphine solution for intrathecal administration. Material and methods: Literature research for published formulations, relevant stability criteria and published stability data. Evaluation of compounding ready-to-administer (RTA) or ready-to-use (RTU) formulations and development of formulation and testing specifications. Development of a stability indicating RP-HPLC method for determining morphine stability and occurrence of degradation products. Three test batches were examined directly after compounding, after sterilisation, on days 14, 30, 60, 150, 200 and 300. Development of a product information and standard operating procedure for clinical use. Results: No published formulations could be found. The pH and oxygen in sterilised solution could be identified as published criteria limiting stability. The shelf-life of prefilled syringes for intrathecal administration (RTA) is limited to 24 hour by the risk of microbial contamination and of extraction of syringe material components. Therefore, the decision was in favour of RTU formulation. A formulation was developed by pharmaceutical principles. Low-dose morphine solution contains morphine hydrochloride trihydrate 100 µg/ml in isotonic sodium chloride solution at pH 2.8–3.3. After filtration, 2.2 ml of the solution is filled in 5 ml injection vials and autoclaved. Stability testing proved the stability of the formulation over at least 300 days. No degradation products were detected. An instruction leaflet, as well as standard operating procedure for safe clinical use of RTU low-dose morphine solution was developed in collaboration with anaesthesiologists and hospital pharmacists Conclusion: Interdisciplinary collaboration of anaesthesiologists and hospital pharmacists enables the development of a simple and stable RTU low-dose morphine formulation for easy application. Patient safety in drug therapy with a high-risk procedure was improved comprehensively. References and/or acknowledgements: McMorrow, et al . Nguyen-Xuan T, Griffiths W, Kern C, et al . No conflict of interest.